Research advances in the construction of stem cell-derived ovarian organoids - Tianyue Zhang; Mengtong Zhang; Sichen Zhang; Shaowei Wang (Stem Cell Research & Therapy)
Abstract Ovarian organoids are essential in female reproductive medicine, enhancing our understanding of ovarian diseases and improving treatments, which benefits women’s health. Constructing ovarian organoids involves two main processes: differentiating induced pluripotent stem cells (iPSCs) into germ and ovarian somatic cells to restore ovarian function and using extracellular matrix (ECM) to create a suitable ovarian microenvironment and scaffold. Although the technology is still in its early stages, future advancements will likely involve integrating high-throughput analysis, 3D-printed scaffolds, and efficient iPSC induction, driving progress in reproductive and regenerative medicine.